Isotope signature and elemental characteristics of subsurface formations around deep-laying coal seams probed by means of atomic and nuclear-based techniques. (September 2022) - Abdelaal, Saad; Hassanin, Walaa; Abdelhady, A.M.; Rashad, A.M.; Kassab, M.F.; Salama, S.; Hamada, Mohamed S.; Elmaghraby, Elsayed K.; Helal, A.I.; Ibraheim, Mona H.
Abstract: A systematic investigation on the isotopic and elemental signature, for both stable and radioactive elements, and mineral contents was performed to examine the characteristics of subsurface formations collected at different depths between 3.962 km and 4.115 km around deep-laying coal seams located under the Marmarica plateau in Egypt. Concentrations of major and minor oxides (Na2 O, MgO, Al2 O3, SiO2, SO3, K2 O, CaO, TiO2, MnO, ΣFeO + Fe2 O3, SrO, ZrO2, and BaO) were determined by X-ray fluorescence and dependencies among these concentrations revealed the type and sort of the formations. Organic contents were determined by Fourier Transform infrared spectroscopy to investigate the variation of the CO/CC bonding ratio with depth. Rare earth elements (REE), specifically Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu were determined by inductively coupled plasma mass spectrometry while actinoids were detected by the radioactive decay of its daughter nuclei. The results showed a high trapping of REE elements and actinoids in layers above the coal seams which indicates the occurrence of aqueous flow followed by possible sorption in these layers. The mobility of the fluid was investigated using the process radioactive decay series between Ra 226 and Ac 228 from one side and their daughters from the other side. Graphical abstract: Image 1 Highlights: Concentration gradient of rare earth elements was found around deep-laying coal seams. Disequilibrium in radioactive decay series is an indication of hydrological effect. Decrease of the infrared signature of CO to CC with depth is observed. Major element correlation showed identification of underground formation. Course of CO2 -based mineral carbonation is possible for long-term sequestration.